Wearable devices may aid the recognition of fluctuation-related pain in Parkinson’s disease—An exploratory, cross-sectional analysis of two prospective observational studies - Katarina Rukavina; Juliet Staunton; Pavlos Zinzalias; Magdalena Krbot Skoric; Kit Wu; Kirsty Bannister; Alexandra Rizos; K. Ray Chaudhuri (PLoS ONE, 2025)
Fluctuation-related pain (FRP) affects more than one third of people with Parkinson’s disease (PwP, PD) and has a harmful effect on health-related quality of life (HRQoL), but often remains under-reported by patients and neglected by clinicians. The National Institute for Health and Care Excellence (NICE) recommends The Parkinson KinetiGraphTM (the PKGTM) for remote monitoring of motor symptoms. We investigated potential links between the PKGTM-obtained parameters and clinical rating scores for FRP in PwP in an exploratory, cross-sectional analysis of two prospective studies: “The Non-motor International Longitudinal, Real-Life Study in PD—NILS” and “An observational-based registry of baseline PKG™ in PD—PKGReg”. 63 PwP (41.3% female; age: 64.24±9.88 years; disease duration, DD: 6.83±5.63 years; Hoehn and Yahr Stage, H&Y: 2 (1–4); Levodopa Equivalent Daily Dose 535 (0–3230) mg) were included. PwP with FRP (n = 23) had longer DD (8.88 (1.29–19.05) vs. 3.16 (0.34–28.92), p = 0.001), higher severity of motor symptoms (H&Y 3 (1–4) vs. 2 (1–4), p = 0.015; SCOPA Motor total score 21.35±10.19 vs. 13.65±8.99, p = 0.003), more dyskinesia (SCOPA Motor Item 18 ≥1 60.9% vs. 7.5%, p<0.001), and worse HRQoL (PDQ-8 Total Score 10.74±5.98 vs. 6.78±5.13, p = 0.007) then PwP without FRP (n = 40). In the multivariate logistic regression, after the adjustment for DD, H&Y and SCOPA-Motor total score, the presence of FRP was significantly associated with the PKGTM-derived Fluctuation-dyskinesia score (Exp (B) = 1.305, 95% CI for Exp (B) 1.012–1.683, p = 0.040) and the Bradykinesia score (Exp (B) = 0.917, 95% CI for Exp (B) 0.842–0.999, p = 0.048). The PKGTM system may potentially advance the way we screen for, assess, and treat FRP in clinical practice.